Consciência argumentativa entre as educadoras Tupinikim de Aracruz-ES que atuam nas primeiras quatro séries do ensino fundamental de escolas indígenas - Almeida, Andréa Cristina (2007)
This Dissertation, Agumentative awereness among Tupinikim educators of Aracruz-ES, teaching in the first grades of the Elementary Indigenous Schools, is focused on the teaching of linguistic argumentative skills developed in two schools of the Comboios and Pau Brasil Tupinikim communities reservations, in Aracruz, Espírito Santo. Initially the Indigenous Education building process within the Brazilian Education and, specifically, in Espírito Santo, is contextualized, within the aim of building a memory of the historical, social and political actions carried out by several Brazilian indigenous peoples, in favor of the construction and implantation of their own way of thinking and acting in the field of education in their own schools. The theoretical basis which the whole research is based upon are the sociohistorical approaches of Bakhtin, Dolz, Scheuwly, Vygotsky and others. Based upon an empirical research, the contents of what is really taught about argumentation in the Tupinikim indigenous schools at the Comboios and Pau Brasil communities is presented. As conclusion of this stady, it is demonstrated how the teaching of argumentation is fundamental for the ethnic background of Tupinikim curumins (children), who are becoming socio-historical subjects and part of the thinking and are the continuity of the acts and thinking people